Analisis Flypaper Effect pada Pengaruh Dana Alokasi Khusus, Pendapatan Asli Daerah dan Sisa Lebih Perhitungan Anggaran terhadap Belanja Daerah di Indonesia (Studi Tahun 2019-2021): Studi Tahun 2019-2021 - Naraswari Wira, Putu Etha; Nyoman Ayu Wulan Trisna Dewi (Universitas Pendidikan Ganesha, 2023)
This research aims to determine the influence of DAK, PAD, and SiLPA on regional spending and to determine whether or not the flypaper effect phenomenon occurred in regional government financial management in Indonesia during the 2019-2021 period. The object of this research includes all regional governments in Indonesia that publish annual APBD realization reports on the website of the Directorate General of Regional Government Financial Balance for 2019-2021. The sample selection in this study used a purposive sampling technique using several considerations according to the desired criteria. The research results show that the DAK, PAD, and SiLPA variables have a significant effect and have a positive relationship with regional expenditure variables. DAK and SiLPA coefficient values < PAD coefficient values. Thus, this shows that there is no flypaper effect on regional government financial management in Indonesia during the 2019-2021 period. The conclusion from this research is that Special Allocation Funds, Original Regional Income, Surplus Budget Calculations have a positive effect on regional spending and the flypaper effect phenomenon does not occur.